2021
DOI: 10.1038/s41467-021-23523-z
|View full text |Cite
|
Sign up to set email alerts
|

Vimentin intermediate filaments stabilize dynamic microtubules by direct interactions

Abstract: The cytoskeleton determines cell mechanics and lies at the heart of important cellular functions. Growing evidence suggests that the manifold tasks of the cytoskeleton rely on the interactions between its filamentous components—actin filaments, intermediate filaments, and microtubules. However, the nature of these interactions and their impact on cytoskeletal dynamics are largely unknown. Here, we show in a reconstituted in vitro system that vimentin intermediate filaments stabilize microtubules against depoly… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 66 publications
4
55
0
Order By: Relevance
“…Furthermore, previous studies have identified ER organizers such as Kinectin, CLIMP63, p180, VIMP, and the long form of STX5, all of which are associated with the microtubule network (Miyazaki, Wakana et al, 2012, Noda et al, 2014, Ogawa-Goto, Tanaka et al, 2007, Shen, Zheng et al, 2019, Vedrenne, 2005). Previously described interplay between Vimentin and microtubule filaments (Gan et al, 2016, Hookway, Ding et al, 2015, Schaedel, Lorenz et al, 2021) or the actin cytoskeleton (Jiu, Lehtimaki et al, 2015, Serres, Samwer et al, 2020) underscores the complexity inherent in the cell’s cytoskeletal foundation. At the same time, our EM reconstruction of the perinuclear region suggests that different types of connections between the ER and various cytoskeletal elements may occur in parallel while we did not observe intense interaction between IF and microtubules.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, previous studies have identified ER organizers such as Kinectin, CLIMP63, p180, VIMP, and the long form of STX5, all of which are associated with the microtubule network (Miyazaki, Wakana et al, 2012, Noda et al, 2014, Ogawa-Goto, Tanaka et al, 2007, Shen, Zheng et al, 2019, Vedrenne, 2005). Previously described interplay between Vimentin and microtubule filaments (Gan et al, 2016, Hookway, Ding et al, 2015, Schaedel, Lorenz et al, 2021) or the actin cytoskeleton (Jiu, Lehtimaki et al, 2015, Serres, Samwer et al, 2020) underscores the complexity inherent in the cell’s cytoskeletal foundation. At the same time, our EM reconstruction of the perinuclear region suggests that different types of connections between the ER and various cytoskeletal elements may occur in parallel while we did not observe intense interaction between IF and microtubules.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have shown that the IF-network can promote migration persistence by modulating microtubule organization and cell polarity [42][43][44] . Whether the absence of GFAPα or dominance of GFAPδ regulates directional migration similarly remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Physical interactions also introduce co-dependent polymerization dynamics of the three cytoskeletal polymers. Branched actin networks reduce the growth rate of microtubules and trigger their depolymerization ( Colin et al, 2018 ), while vimentin filaments bind to microtubules and stabilize them against depolymerization ( Schaedel et al, 2021 ) and also bind to actin filaments ( Esue et al, 2006 ). In the presence of crosslinkers and motors, the three filament systems can additionally co-align and (re-)direct each other’s polymerization direction ( Preciado López et al, 2014 ; Gan et al, 2016 ; Leduc and Etienne-Manneville 2017 ).…”
Section: Contributions Of Cytoskeletal Crosstalk To Force Transmissio...mentioning
confidence: 99%